Transcription factor ZBTB42 is a novel prognostic factor associated with immune cell infiltration in glioma - Li, Yanwen; Zhu, Yongwei; Chen, Long; Xia, Shunjin; Adegboro, Abraham Ayodeji; Wanggou, Siyi; Li, Xuejun (Frontiers in Pharmacology, 2023)
Background: ZBTB42 is a transcription factor that belongs to the ZBTB transcript factor family and plays an important role in skeletal muscle development. Dysregulation of ZBTB42 expression can lead to a variety of diseases. However, the function of ZBTB42 in glioma development has not been studied by now. Methods: We analyzed the expression of ZBTB42 in LGG and GBM via the TCGA (The Cancer Genome Atlas) database. GO, KEGG, and GSVA analyses were performed to illustrate ZBTB42-related pathways. ESTIMATE and CIBERSORT were applied to calculate the immune score and immune cell proportion in glioma. OCLR algorithm was used to study the stemness of glioma. Multivariate Cox analysis was employed to detect the prognostic value of 5 ZBTB42-related genes. Results: Our results show that ZBTB42 is highly expressed in glioma and may be a promising prognostic factor for LGG and GBM. In addition, ZBTB42 is related to immune cell infiltration and may play a role in the immune suppression microenvironment. What’s more, ZBTB42 is correlated with stem cell markers and positively associated with glioma stemness. Finally, a five genes nomogram based on ZBTB42 was constructed and has an effective prognosis prediction ability. Conclusion: We identify that ZBTB42 is a prognostic biomarker for LGG and GBM and its function is related to the suppressive tumor microenvironment and stemness of glioma.